Validity and Reliability of Practical Teaching Practice Instruments among Construction Technology Lecturers in Vocational Colleges - Halimoon, Hasrul; Ibrahim Mukhtar, Marina; Roddin, Rohayu (Journal of Technical Education and Training, 2021)
Practical teaching practice is one of the important aspects of Technical and Vocational Education and Training (TVET). This study aimed to identify the validity and reliability of lecturers’ teaching practice instrument in construction technology at vocational colleges by using a mixed method which was quantitative and qualitative analysis. The instruments comprised a questionnaire, observation review, and interview protocol that were modified to ensure compliance with the set objectives. The instrument was implemented based on predetermined procedures and it met the measurement standards for validity and reliability. The research conducted content validity and face validity on the constructed questionnaire, either by using construct determination, expert validation, or factor analysis for quantitative methods. Meanwhile, qualitative validity was implemented by triangulation, expert evaluation, and a review by the pilot study participants. The overall findings showed a high level of validity after some improvements were implemented. The findings of the Cronbach’s alpha test for reliability analysis showed 0.90 and above for each item that was determined. Meanwhile, for qualitative study Cohen kappa analyses yielded a value of 0.87 for interviews and 0.83 for observations. This showed a high level of validity and reliability of the study instrument and thus it could be used in the actual study.